P-small Compressible Modules and P-small Retractable Modules - ALHakeem, Mohammed Baqer; Al-Mothafar, Nuhad Salim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Let be a commutative ring with 1 and be left unitary . In this papers we introduced and studied concept P-small compressible (An is said to be P-small compressible if can be embedded in every of it is nonzero P-small submodule of . Equivalently, is P-small compressible if there exists a monomorphism , , is said to be P-small retractable if , for every non-zero P-small submodule of . Equivalently, is P-small retractable if there exists a homomorphism whenever as a generalization of compressible and retractable respectively and give some of their advantages characterizations and examples.